The ankle joint dorsiflexion range of motion in the closed kinematic chain of judokas and football players - pilot study - Líška, D.; Liptaková, E.; Batalik, L.; Rutkowski, S. (Archives of Budo, 2021)
Background and Study Aims: Judo is a sport that requires combination of multiple demanding training attributes. Little is known about the impact of a long-term practice on the ankle joint dorsiflexion range of motion. The aims of this pilot study is knowledge about dorsiflexion range of motion in the judokas in comparison to the football players. Material and Methods: The sample included 20 judokas with a mean age of 20.15 years (±4.17). The mean weight of the judokas was 82.15 kg (±15.5). The mean height of the judokas was 180.40 cm (±7.46). The control group consisted of 22 football players with a mean age of 21.63 (±3.40). The mean weight of the football players was 75.90 kg (±6.67). The mean height of the football players was 181.27 cm (±5.86). Results: The mean right ankle joint dorsiflexion range of motion in judokas was 43.15° ( ±6.71). The mean right ankle joint dorsiflexion range of motion in football players was 41.02° (±5.72). The mean left ankle joint dorsiflexion range of motion in judokas was 43.90° (± 6.68). The mean left ankle joint dorsiflexion range of motion in football players was 42.09° ( ±7.17). Non-significant difference was finding between groups in right (p = 0.357) or left (p = 0.284) ankle joint dorsiflexion range of motion. Conclusions: Greater ankle joint dorsiflexion range of motion was found in judokas. Better adaptation in favour of the judokas means greater variability in the movement of the ankle towards the dorsiflexion in the judoist training process. Judo leads to better adaptation in the ankle joint towards dorsiflexion in ankle joint in compared to football players. However, results were no statistically significant.